Phronesis and Resource Curse Hypothesis in Post-Independent Sierra Leone - Emerson Abraham Jackson (Ilorin Journal of Economic Policy, 2016)
This study was undertaken with a view of presenting a balanced critical discourse on the concept of Phronesis as applied in the political economy of Sierra Leone. The country is renowned for being endowed with the abundance of non(renewable) natural resources, while at the same time for poor management of resources which has given rise to its classification under the brand name of 'resource curse or Dutch disease'. Based on critical phenomenological discourses of scholarly literature and the analytical hermeneutics of secondary data collected, evidence to some extent have pointed to the fact that both colonial and post-independence governance contributed immensely to the resource curse syndrome in Sierra Leone; a situation where poor management of natural resources has been a disaster, rather than a blessing in the country's sustained pathway of development. The paper thus conclude that Sierra Leone, is capable of recovering from the alleged symptom of 'resource curse/Dutch disease', but only in a situation where the rule of law is effectively applied with perpetrators of unethical acts leading to the exploitation of natural (non) renewable resources are (severely) punished to deter future cases of unethical practices. – – Cette étude a été entreprise dans le but de présenter un discours critique équilibré sur le concept de Phronesis tel qu'il est appliqué dans l'économie politique de la Sierra Leone. Le pays est réputé pour être doté avec l'abondance de ressources naturelles non renouvelables (en même temps que la mauvaise gestion des ressources qui a donné lieu à sa classification sous la marque «Resource Curse» ou «Dutch maladie'. Basé sur des discours phénoménologiques critiques de la littérature savante et de la l'herméneutique des données secondaires collectées, des preuves dans une certaine mesure ont montré que et la gouvernance post-indépendance a énormément contribué au syndrome de la malédiction des ressources en Sierra Leone; une situation où la mauvaise gestion des ressources naturelles a été une catastrophe, plutôt qu'une bénédiction dans le voie de développement durable du pays. Le document conclut ainsi que la Sierra Leone est capable de se remet du symptôme présumé de «malédiction des ressources / maladie hollandaise», mais seulement dans une situation où la règle de droit est effectivement appliquée avec les auteurs d'actes contraires à l'éthique menant à l'exploitation de la nature les ressources (non) renouvelables sont (sévèrement) sanctionnées pour dissuader de futurs cas de pratiques contraires à l'éthique.
Keywords: F50; N57; P16; 330; Phronesis; Paradox of Plenty; Political Economy; Sierra Leone